The Boxer Movement and the Disputes between the Medieval China and the Modern West from the Perspective of the Conflict between Eastern and Western Civilization - LI, Anze (Journal of Research for Christianity in China (JRCC), 2023)
The Boxer Movement is the result of contradictions between the Late-Qing China and the Western powers since the modern time. Apparently, it is the common people represented by the Boxers who wanted to resist the invasion of Western colonialism with "divine fist" and the folk culture. In essence, it is a conflict between the Chinese Confucian civilization and the Western Christian civilization. Also, it could be taken as a landmark of the outbreak of the conflict between Eastern and Western civilizations. The fact that the Boxer Movement failed irrefutably proves that the dispute between China and the West is a dispute between the Medieval and the Modern. As a result, the Boxer Movement became the turning point of Chinese history from the Medieval to the Modern, inspiring those who want to constantly think over the topic of civilization conflict and dialogue.